The Effect of Electronic Word of Mouth (E-WOM) and Positive Image on Interest in Voting for Gibran Rakabuming Raka in the 2020 Solo Pilkada (Research Study on the Millennial Generation in Solo City) - Rifki Aulia; Andrik Purwasito; Sri Hastjarjo (Formosa Journal of Social Sciences (FJSS), 2023)
Electronic word of mouth and positive image is among the methods that can be used to promote oneself in the 2020 elections without a direct campaign. This study aims to analyze the impact of e-wom, new media, social media, and positive image as a campaign tool by the 2020 Libertadores of Surakarta mayor and with mayor Gibran Rakabuming Raka and the practice firm. This type of research is a quantitative method of surveying using berganda linear analytics, followed by validity and religious testing tests to test variable worthiness. The emphasis of this study was the people of the city of Surakarta z and the millennial generation since 21-41. (1) variables (x1) electronic word of mouth by Surakarta city on social media can significantly impact the selective interest, judging from regression coefficient value of 0.259 and a significant number of.000< 0.05 appears small. (2) variables (x2) also have a positive and significant impact on the selective interest, this can be seen from the large positive regression value of 0.652 and a significant number of.000< 0.05 appears smaller. The conclusion may be made that e-wom and positive image significantly impact the interest in selecting couples for mayors and 2020 vice mayor of Surakarta